Integration of high-thermal-responsive color change and invisible emission intensity ratio in Gd2Mo4O15 lattice with the desired structure. (January 2023) - Xing, Mingming; Pang, Tao; Yan, Liqing; Kang, Lihua; Wu, Xingyu; Wang, Hong; Fu, Yao; Luo, Xixian; Tian, Ying
Abstract: Thermal-responsive upconversion luminescence (UCL) is of interest due to its potential application in anti-counterfeiting and temperature sensing. However, integrating the multi-model emission intensity ratios with high-thermal sensitivity, especially those involving invisible UCL, into a single host lattice remains challenging. In this work, the color change of blue to bluish-purple and invisible emission intensity ratio with a temperature sensitivity as high as 13.47% K −1, thanks to the crossover-reduced thermal quenching and the Yb 3+ -MoO4 2- dimer sensitization, are available in the monoclinic Gd2 Mo4 O15 :Yb 3+ /Tm 3+ . Moreover, the temperature-dependent color response is tunable, such as the introduction of Er 3+ results in a color change from blue to bluish-green. Our results allow promising temperature-dependent UCL applications and open the opportunity for other functional materials based on Re2 Mo4 O15 with desirable phase structures. Highlights: Thermal-responsive color change are observable in the monoclinic Gd2 Mo4 O15 through doping with Yb 3+ /Tm 3+ or Yb 3+ /Tm 3+ /Er 3+ . Invisible emission intensity ratio with a sensitivity of 13.47% K −1 is available in the monoclinic Gd2 Mo4 O15 :Yb 3+ /Tm 3+ . The controllable synthesis of Gd2 Mo4 O15 with two distinct phase structures is revealed.